Efficiency of combined endocrine therapy with CDK4/6 inhibitors in metastatic HR+/HER2- breast cancer: Immunological aspects - A. V. Sultanbaev; I. A. Tuzankina; I. V. Kolyadina; A. F. Nasretdinov; Sh. I. Musin; N. I. Sultanbaeva; K. V. Menshikov; A. A. Izmailov; M. V. Sultanbaev; D. A. Kudlay (Медицинская иммунология, 2025)
Luminal HER2-negative subtypes of breast cancer have always attracted oncologists due to their sensitivity to low-toxicity hormone therapy. The emergence of new inhibitors of cyclin-dependent kinases has allowed hormone therapy to achieve optimal control of tumor growth, being prescribed even for visceral lesions. Recent advances in this area have provided novel mode of hormonal therapy as the first-line standard for extended HR+/HER2- breast cancer. Evaluation of the relationship between tumor progression and immune surveillance was more often associated with the triple-negative subtype characterized by relatively high levels of mutational load and tumor-infiltrating lymphocytes. However, data from some studies suggest a possible relationship between immunity and luminal types of breast cancer. On the basis of these conclusions, the aim of our work was to evaluate different immunological and clinical factors in view of effectiveness of combined endocrine therapy with CDK4/6 inhibitors in metastatic luminal HR+/HER2- breast cancer, primarily in the context of assessing immune deficiency conditions by the levels of T-cell receptor excision circles (TREC) and κ-deletion element of B cells (KREC). The study included 51 patients with luminal HER2-negative breast cancer who received combined endocrine therapy with CDK4/6 inhibitors. The results of the study indicated a decrease in TREC levels with increasing patients’ age. A decrease in the absolute number of TREC was noted in peripheral blood of patients with worse treatment outcomes, i.e., insufficient response to therapy, rapid progression or death, along with significant intercorrelation between lethal outcomes and low levels of B cell κ-deletion element (KREC) thus suggesting an important role of these immune factors in clinical prognosis. Hence, we consider prognostic significance of T cell receptor excision rings in the patients’ peripheral blood. This factor may affect treatment outcomes and survival rates.